AGILITY IN ORGANIZATIONAL PROCESSES: A NEW APPROACH TO CREATING COMPETITIVE ADVANTAGE - Rezapour-Nasrabad, Rafat (International Journal of Psychosocial Rehabilitation, 2020)
Agility is critical to the success of today's businesses, but rapid, thoughtless developments are fragile. Every organization including health organizationes must be capable of producing or serving different, short-lived products simultaneously, redesigning products or sevices, changing production methods, and responding effectively to environmental changes. One of the key factors in creating agility for every organizations is using an advanced technology interact effectively to fulfill the needs of customers. By using the right tools, it is possible to anticipate and meet needs and create a positive cycle of product and service creation and this makes it successful in competition. in an agile process, all individuals, institutions and organizational processes interact seamlessly, by utilizing the advanced technology to meet customer needs. Indeed, agility means the ability and speed of action of an organization for rapid and simultaneous application and interaction of technology, employees and management via creating rapid communicative infrastructures in purposeful, efficient and planning accountability and continuous and unpredicted changes in the needs of customers and market environmental conditions with the timely detection of opportunities. In an agile process, technology, management and personnel of organization as purposeful and planned interact in a dynamic environment in terms of unpredicted changes for rapid response to these changes. In this mini review study, after review of the existing studies and electronic search in the local and international resources regarding to organizational agility, the researcher could explain the structure of agile or process oriented organizations.